2020
DOI: 10.1016/j.psj.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Light emitting diode (LED) color and broiler growth: effect of supplementing blue/green LED to white LED light on broiler growth, stress, and welfare

Abstract: Light emitting diode ( LED ) lighting provides an affordable lighting option for use in commercial poultry production. However, more information is needed to understand the effects of LED color on broiler welfare and growth. Five consecutive flocks (1 in summer, 1 in fall, 2 in winter, and 1 in spring) of straight run Ross 708 × Ross 708 broilers were reared in commercial type barns for 45 D. For white only ( WO ) treatment, birds were reared under white LED only (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…At the age of 42 days, the F/G of the BG group was significantly lower than that of other experimental groups, and the advantage of the BG group on the production performance of 42-day-old broilers was better than that of the W and G groups, which represents the advantage of blue-green composite light to reduce F/G and improve broiler performance. It has been shown that combining the advantages of monochromatic light can affect the growth of broilers [11,21]. Similarly, the blue-green composite light selected in this experiment realized the growth promotion of broilers.…”
Section: Growth Performancementioning
confidence: 76%
See 1 more Smart Citation
“…At the age of 42 days, the F/G of the BG group was significantly lower than that of other experimental groups, and the advantage of the BG group on the production performance of 42-day-old broilers was better than that of the W and G groups, which represents the advantage of blue-green composite light to reduce F/G and improve broiler performance. It has been shown that combining the advantages of monochromatic light can affect the growth of broilers [11,21]. Similarly, the blue-green composite light selected in this experiment realized the growth promotion of broilers.…”
Section: Growth Performancementioning
confidence: 76%
“…The current research showed that blue light and green light are more conducive to the growth of the broilers because green or blue light can significantly promote the myogenic process of satellite cells [9,10]. In addition to monochromatic light, the study of combined monochromatic light showed that white LED supplemental blue/green LED or switching light from green (blue) to blue (green) leads to further weight gain in broilers [11,12].…”
Section: Introductionmentioning
confidence: 79%
“…Satisfactory results using white LED light on chicks were reported [8], whereas another study reported no effect on body weight [28]. In more recent research, the different white LED light colors increased activity when compared to blue or green light, showing that light color has an impact on the chick's behavior [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, broilers chickens reared under blue and green monochromatic light experienced increased BW compared to broilers exposed to white or red light [22][23][24][25]. Moreover, Nelson, et al [26] found that Ross 708 broilers reared under white LED supplemented with blue/green light had higher overall day 45 live body weight than birds reared under only white LED light.…”
Section: Performance Traitsmentioning
confidence: 99%